Analysis of Water Flow Rate in the Kemiri River, Jayapura District - Yoku, Rosdiana; Irawan, Sakka; Kopeuw, Agnes Julia; Haay, Happy Alyzhya; Daullu, Melissa Aeudia (Universitas Cenderawasih, 2025)
Kali Kemiri Sentani frequently experiences flooding, particularly during periods of intense rainfall. Given the critical importance of flood risk mitigation, this study aims to analyze the water flow rate in Kali Kemiri and investigate the key factors influencing its dynamics. The research was conducted within the Kali Kemiri watershed in Jayapura Regency, focusing on a watershed area with a total study area of 1,640 m², mapped at a small scale across two measurement points. Flow rate measurements were performed at two locations along Kali Kemiri using the float method. The study recorded key hydrological parameters, including water depth, river width, and flow velocity. These data were utilized to calculate the volumetric flow rate at the designated measurement sites. This methodology provides a comprehensive understanding of the hydrodynamic factors affecting water flow, which is essential for assessing flood hazards in the region. The results indicate that the highest discharge rate was observed at the first measurement point, with an average flow discharge of 0.188 m³/s and a velocity of 0.52 m/s. In contrast, the second measurement point recorded a discharge of 0.115 m³/s with a flow velocity of 0.29 m/s. These findings suggest a direct correlation between flow velocity and discharge, wherein an increase in velocity corresponds to an increase in discharge. Furthermore, the study highlights that the flow rate is influenced by watershed area, watershed volume, and watershed slope, which collectively govern the hydrological behavior of the river system.